Supporting Interpersonal Interaction during Collaborative Mobile Search - Teevan, Jaime; Morris, Meredith Ringel (IEEE Computer, 2014)
O-SNAP is a mobile application that explicitly supports in-person collaborative search by enabling users to physically signal their willingness to share and by facilitating face-to-face search-related communication. The Web extra here is a video in which author Meredith Ringel Morris discusses scenarios that can prompt collaborative information seeking.